Bortezomib Rescues Ovariectomy-Induced Bone Loss via SMURF-Mediated Ubiquitination Pathway. (31st December 2021) - Fang, Yuepeng; Liu, Yang; Zhao, Zhijian; Lu, Yingjie; Shen, Xu; Zhu, Tianfeng; Hou, Mingzhuang; He, Fan; Yang, Huilin; Zhang, Yijian; Shi, Qin; Zhu, Xuesong
Abstract : A balance between bone formation by osteoblasts and bone resorption by osteoclasts is necessary to maintain bone health and homeostasis. As a cancer of plasma cells, multiple myeloma (MM) is accompanied with rapid bone loss and fragility fracture. Bortezomib has been used as a first-line for treating MM for decades. Recently, the potential protection of bortezomib on osteoporosis (OP) is reported; however, the specific mechanism involving bortezomib-mediated antiosteoporotic effect is undetermined. In the present study, we assessed the effects of in vitro bortezomib treatment on osteogenesis and osteoclastogenesis and the protective effect on bone loss in ovariectomized (OVX) mice. Our results indicated that bortezomib treatment increased osteogenic differentiation of MC3T3-E1 cells as evidenced by increased levels of matrix mineralization and osteoblast-specific markers. In bortezomib-treated bone marrow monocytes (BMMs), osteoclast differentiation was suppressed, substantiated by downregulated tartrate-resistant acid phosphatase- (TRAP-) positive multinucleated cells, areas of actin rings, pit formation, and osteoclast-specific genes. Mechanistically, bortezomib exerted a protective effect against OP through the Smad ubiquitination regulatory factor- (SMURF-) mediated ubiquitination pathway. Furthermore, in vivo intraperitoneal injection of bortezomib attenuated the bone microarchitecture in OVX mice. Accordingly, our findings corroborated that bortezomib might have future applications in the treatment of postmenopausal OP.